Nine new species of the subgenus Stegana (Steganina) from China, with DNA barcoding information (Diptera: Drosophilidae) - Li, Bingxue; Zhang, Yuan; Chen, Hongwei (Zootaxa, 2019)
Eleven (two known and nine new) species of the subgenus Stegana (Steganina) from China are described or redescribed: S. (S.) longifibula Takada, 1968, S. (S.) toyaensis Okada & Sidorenko, 1992, S. (S.) biflava sp. nov., S. (S.) flavivittata sp. nov., S. (S.) hirtifoliacea sp. nov., S. (S.) latitabula sp. nov., S. (S.) panda sp. nov., S. (S.) pinguifoliacea sp. nov., S. (S.) spatulata sp. nov., S. (S.) stachydifolia sp. nov. and S. (S.) unguiculata sp. nov.; they are assigned into the coleoptrata, ornatipes and undulata species groups, respectively. A total of 130 DNA sequences of partial mitochondrial cytochrome c oxidase subunit I (mtCOI) gene of 38 species (including the 11 species) of above-mentioned three groups are newly obtained in this study. These sequences and other available barcoding sequences of the three groups are involved in a molecular analysis using neighbor-joining (NJ) method, in order to assess the availability of DNA barcoding for delimiting the Steganina species. The result indicates that all the sampled Steganina morphospecies within the three groups are monophyletic.